The role of polymerization in adhesive dentistry. Issue 1 (January 2019) - Cadenaro, Milena; Maravic, Tatjana; Comba, Allegra; Mazzoni, Annalisa; Fanfoni, Lidia; Hilton, Tom; Ferracane, Jack; Breschi, Lorenzo
Highlights: Factors that influence polymerization of adhesives are described. Accurate evaporation of the solvents may improve the polymerization of adhesive system. Prolonged curing time increase the performance and stability of adhesive systems. The effect on curing reaction of molecules added to adhesive formulations to counteract the degradation of the adhesive interface over time has to be clarified. Abstract: Adhesive systems are resin-based materials that reach their final mechanical properties through a polymerization process. Previous literature correlated the failure of the adhesive interface to low polymer setting. Adhesives systems are elaborate mixtures of different molecules of both hydrophilic and hydrophobic nature, included in the formulation to adequately infiltrate the complex dental substrate or added to prolong the stability of the adhesive layer over time. Each adhesive component may influence the polymerization reaction of the material. Photopolymerization is a complex reaction that has several clinical implications, and besides the material composition, it is influenced by multiple factors, including the substrate characteristics, the operator technique, and the light cure unit properties. This review is focused on the analysis of factors that have a potential role in the setting of adhesive materials and thus the ultimate characteristics of the adhesive layer and the stability of the resin-dentin interface.